Synthesis and Characterization of Poly(acrylamide) Hydrogels as pH and Salt Sensitive Material - Thippeswamy, Madhusudana; Ganjeenahalli Puttagiddappa, Mamatha; Thippaiah, Demappa; Devappa Satyanarayan, Nayak (Asian Journal of Chemistry, 2021)
This work reports the synthesis of poly(acrylamide) hydrogel and its characterization. Hydrogel will be synthesized by a chemical cross-linking method using sodium metabisulfite and potassium persulphate as initiators with crosslinker methylenebisacrylamide. The synthesized hydrogels were examined by FT-IR, SEM and TGA to determine chemical interactions in the polymer network. Moreover, the swelling study explains that hydrogels swelling capacity and it depends on the concentration of the crosslinking agent. The pH, temperature and salt solutions will impact on swelling properties. In acid and base solutions, the swelling ratio order is as follows HCl < CH3COOH < HClO4 < NaOH and the swelling ratio order in salt solutions is as follows: NaCl > CaCl2 > AlCl3.